RANCANG BANGUN DAN PENERAPAN APLIKASI ANDROID PENGENALAN HEWAN-HEWAN BERSUARA UNTUK ANAK USIA DINI - PUJI ASTUTI (Faktor Exacta, 2016)
The purpose of this research was to design an application that can help recognize animal noises that specialize in the school kids kindergarten. The research method used by writer is method grounded (grounded research) is a research method based on the facts and using a comparative analysis with the aim of holding an empirical generalization, establish the concept, to prove the theory, at the same time. In this research data is the source of the theory or theories based on the data. The author can draw the conclusion that the application design animals voiced android-based, it can be used as a benchmark as the progress of perception and memory of children. The result can be more like a child's learning and learning fast to understand this. Keyword: Android, Animal, Early age